Types of Betula (Betulaceae) names described from Ukraine and deposited in the National Herbarium of Ukraine (KW) - Olshanskyi, I.G.; Shyian, N.M.; Tarieiev, A.S. (Український ботанічний журнал, 2016)
The article provides data about authentic materials of Betula (Betulaceae) names described from Ukraine and deposited at the National Herbarium of Ukraine (KW). For each taxon, its protologue, synonyms and text of the label are presented. We designate here lectotypes of Betula borysthenica Klokov, B. klokovii Zaverucha, and report the holotype of B. kotulae Zaverucha, and authentic materials of B. klokovii Zaverucha, B. polessica Ivchenko etc.